Distributions of polychlorinated naphthalenes in beef from China and associated health risks. (1st April 2023) - Dong, Shujun; Li, Jingguang; Zhang, Lei; Zhang, Su; Zou, Yun; Zhao, Yunfeng; Wu, Yongning; Wang, Peilong
Abstract: Polychlorinated naphthalenes (PCNs) are toxic and can accumulate through the food chain. PCNs have been detected in different categories of foods. Intake of animal-derived foods is an important pathway for human exposure to PCNs. However, information on PCNs in meat from farmed animals is scarce. In this study, PCNs were assessed in beef sourced from local markets in Beijing and six provinces in China. The mean PCN concentrations in beef samples from the seven regions varied from 41.2 to 88.7 pg/g wet weight (ww). The homologue profiles of PCNs in the specimens were similar, with tri- and di-CNs being dominant. The mean concentration of PCNs in the flank (74.7 pg/g ww) was higher than that in the round (58.2 pg/g ww) or shank (53.6 pg/g ww), likely because the former contained a higher proportion of lipids than the latter. Significantly different PCN distributions in beef and dairy cow milk were identified using machine learning. The toxic equivalencies (TEQs) of PCNs in all beef samples ranged from 0.0003 to 0.022 pg TEQ/g ww. PCNs contributed to approximately 4.6% of the total TEQ values of polychlorinated dibenzo- p -dioxins, polychlorinated dibenzofurans, polychlorinated biphenyls, and PCNs in the beef. Health risks related to the intake of PCNs through beef consumption by the average person living in China were minimal. Graphical abstract: Image 1 Highlights: PCN homologue profiles in beef from different regions of China were similar. PCN concentrations in flank were higher than in round and shank. Variations in lower chlorinated PCN congeners between beef and milk were identified. PCN contributions to total TEQs were lower than those of other dioxin-like compounds. The risks of exposure to PCNs through beef consumption in China are low.